Landscape spatial configuration influences phosphorus but not nitrate concentrations in agricultural headwater catchments. Issue 2 (8th February 2023) - Dupas, Rémi; Casquin, Antoine; Durand, Patrick; Viaud, Valérie
Abstract: Landscape organized (or structured) heterogeneity influences hydrological and biogeochemical patterns across space and time. We developed landscape indices that describe the spatial configuration of nutrient sources and sinks as a function of their hydrological distance to the stream (lateral dimension) or to the outlet (longitudinal dimension) and their intersection with flow‐accumulation areas. Using monthly nitrate, total phosphorus (TP), soluble reactive phosphorus (SRP) and daily discharge (Q) data from 221 rural catchments (1–300 km 2 ) from 2010–2020, we observed higher variability in flow‐weighted mean concentrations in smaller catchments than in larger ones. The variability in landscape configurations also decreased with increasing catchment size. A landscape configuration index, calculated as mean arable land use weighted by spatial data on hydrological distance and flow accumulation, improved prediction of TP and SRP, but not nitrate, compared to the unweighted mean arable land use. We conclude that landscape configuration influences phosphorus transfer more than nitrate transfer, and that flow‐accumulation zones and riparian areas are critical source areas for TP and SRP, respectively. By contrast, landscape spatial configuration in the lateral (upslope–downslope) and longitudinal (upstream–downstream) dimensions did not have an identifiable influence on nutrients temporal dynamics. The indices developed in this study can help design landscapes that minimize diffuse phosphorus losses to streams and show that landscape management is not a first order control for nitrate losses. Abstract : We developed landscape indices that describe the spatial configuration of nutrient sources and sinks as a function of their hydrological distance to the stream or to the outlet and their intersection with flow‐accumulation areas. Landscape configuration influences phosphorus transfer but not nitrate transfer.